Chemical reactions with the Casson nanofluid flow by the bioconvective behavior of microorganisms over a spinning disc - Prabhakar Sagadevan; Umadevi Raju; Meganathan Murugesan; Unai Fernandez-Gamiz; Samad Noeiaghdam (Heliyon)
This study examines the behavior of the Casson nanofluid bioconvection flow around a spinning disc under various influences, including gyrotactic microorganisms, multiple slips, and thermal radiation. Notably, it accounts for the reversible nature of the flow and incorporates the esterification process. The aim of this study is to investigate the influence of reversible chemical reactions on the flow behavior of a Casson nanofluid in the presence of bioconvective microorganisms over a spinning disc. Specifically, the study seeks to understand how the non-Newtonian rheology of Casson fluids, enhanced by nanoparticles, affects heat and mass transfer and how bioconvection driven by motile microorganisms impacts the reaction kinetics and fluid dynamics. The significance of studying chemical reactions in Casson nanofluid flow with bioconvective microorganisms over a spinning disc lies in its broad applicability to fields such as chemical engineering, biomedical engineering, environmental science, and nanotechnology. Using the right variables to change the nonlinear partial differential equations (PDEs) that govern the problem into a system of ordinary differential equations (ODEs) is a key step toward finding numerical solutions. Using numerical methods such as the bvp4c approach, the study explores the solutions to these intricate equations. Key focus areas include assessing the impacts of different parameters on the thermal field, nanoparticle concentration, and microbiological field. Graphical representations provide information on the velocity, temperature, concentration, and microorganism profiles, elucidating the underlying physical effects. Furthermore, the study evaluates the wall shear stress, the local Nusselt number, the local Sherwood number, and the local motile density number, providing graphical explanations to elucidate these phenomena. Notably, it highlights the distinction in the rate of the motile density number between reversible and irreversible flows concerning Brownian motion and Peclet number. The findings of the theoretical simulations have significant implications for biotechnology and thermal engineering, offering dynamic insights into practical applications within these fields.